Konsep Manajemen Mutu Pendidikan Islam - Ravika Hadi (Yayasan Rahmat Islamiyah, 2021)
This journal focuses on the Quality of Educational Institutions through Quality Management in Schools. The problem of education quality is one of the central issues in national education, especially related to the low quality of education at every level and education unit, especially in primary and secondary education. Realizing this, the government has made various efforts to improve the quality of national education, including through various trainings and improving the quality of teacher competencies, procuring books and learning media, improving educational facilities and infrastructure, and improving the quality of school management. So that the concept of